Japan's Public Sector Balance Sheet - Koshima, Yugo (IMF Working Papers; Working Paper ;, 2019)
This paper compiles and reviews the evolution of Japan's Public Sector Balance Sheet (PSBS). In the past, large crossholdings of assets and liabilities within the public sector played a role in sustaining a high level of public debt and low interest rates. The Fiscal Investment and Loan Fund (FILF) channeled all postal deposits and pension savings to financing of public sector borrowing. After the FILF refrom in 2000, however, the Post Bank and pension funds shifted their assets to the portfolio investments and are seeking to maximize risk-adjusted returns. This has changed the implications of crossholdings for public debt management. In the future, population aging is expected to add more pressures on the PSBS, which already saw a considerable decrease of net worth over the last three decades.